IMPACT OF RESIDENTIAL HEATING COSTS ON THEIR VALUE - Nalewajko, Marta (Economics and Environment, 2021)
This article deals with the essence of the influence of factors related to various heat sources on property valuation. The study’s main aim is to show that the applied heating system impacts the costs of maintaining and operating a building. A thesis was made that the type of heat source used to heat the property is a factor that significantly influences the value because its efficiency and general characteristics can significantly affect the amount of the building’s operating costs. For this reason, the method of heating building objects should be an attribute taken into account during the valuation carried out by a property appraiser.